2022
DOI: 10.5498/wjp.v12.i10.1298
|View full text |Cite
|
Sign up to set email alerts
|

Overlap of orthorexia, eating attitude and psychological distress in some Italian and Spanish university students

Abstract: BACKGROUND Orthorexia nervosa (ON) is the persistent concern of maintaining the self-imposed diet to improve one's health. Many factors have been associated to ON in univ-ersity students. AIM To assess the prevalence of ON in Italian and Spanish university students in relation to eating attitude and psychological distress, and the possible overlaps between ON (evaluated with different scored questionnaires from the originally proposed ORTO-15), distress and risk of eati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 55 publications
1
9
1
Order By: Relevance
“…In this systematic review and meta-analysis, 34 studies used the <35 cutoff point [ 20 , 29 , 30 , 33 , 37 , 38 , 40 , 41 , 46 , 49 , 55 , 56 , 59 , 60 , 64 - 67 , 69 - 71 , 73 - 77 , 81 - 84 , 88 , 90 , 92 , 93 , 96 ], 64 studies used the <40 cutoff point [ 10 , 20 , 29 - 39 , 42 - 45 , 47 - 54 , 56 - 58 , 61 - 65 , 68 , 70 , 72 - 76 , 78 - 101 ], and 23 studies used both cutoff points [ 20 , 29 , 30 , 33 , 38 , 49 , 56 , 64 , 65 , 70 , 73 - 76 , 81 - 84 , 88 , 90 , 92 , 93 , 96 ]. Based on the <35 cutoff point, all the studies were cross-sectional.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this systematic review and meta-analysis, 34 studies used the <35 cutoff point [ 20 , 29 , 30 , 33 , 37 , 38 , 40 , 41 , 46 , 49 , 55 , 56 , 59 , 60 , 64 - 67 , 69 - 71 , 73 - 77 , 81 - 84 , 88 , 90 , 92 , 93 , 96 ], 64 studies used the <40 cutoff point [ 10 , 20 , 29 - 39 , 42 - 45 , 47 - 54 , 56 - 58 , 61 - 65 , 68 , 70 , 72 - 76 , 78 - 101 ], and 23 studies used both cutoff points [ 20 , 29 , 30 , 33 , 38 , 49 , 56 , 64 , 65 , 70 , 73 - 76 , 81 - 84 , 88 , 90 , 92 , 93 , 96 ]. Based on the <35 cutoff point, all the studies were cross-sectional.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies did not specify the country since it was performed via social media [ 64 , 92 ]. Two studies were conducted in two countries [ 30 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lakritz et al (2022) used the ORTO–15 but did not use the original scoring procedure proposed by Donini et al (2005) but scored items based on the factor analysis reported by Meule et al (2020). These inconsistencies are particularly crucial when studies provide prevalence estimates of ON, which have been found to be unrealistically high and very different across studies that used the ORTO–15 and its derivatives (e.g., Aiello et al, 2022; Bergonzi & Massarollo, 2022; Kujawowicz et al, 2022). Thus, even when using short forms of the ORTO–15 or different scoring procedures leads to better psychometric properties in terms of internal reliability and factorial validity, this does not mean that this leads to an improved, growing knowledge about ON as findings cannot be accumulated across different studies.…”
Section: Assessment Of Onmentioning
confidence: 99%
“…Lakritz et al (2022) used the ORTO-15 but did not use the original scoring procedure proposed by Donini et al (2005) but scored items based on the factor analysis reported by Meule et al (2020). These inconsistencies are particularly crucial when studies provide prevalence estimates of ON, which have been found to be unrealistically high and very different across studies that used the ORTO-15 and its derivatives (e.g., Aiello et al, 2022;Bergonzi & Massarollo, 2022;Kujawowicz et al, 2022). Thus, even when using short forms of the ORTO-15 or different scoring procedures leads to better psychometric properties in terms of internal reliability and factorial validity, this does not mean that this leads to an improved, growing knowledge about ON as findings cannot be accumulated across different studies.…”
Section: Introductionmentioning
confidence: 99%